Revisi Strategi dalam Entitas yang Ada (Studi Kasus pada Perusahaan Gondola PT. XYZ) - Lauw, Nancy Lociana Oktaviani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This thesis provides an understanding of the importance of strategic management as a part of business management. Through case study of an existing medium-sized enterprise, a standard strategic management framework is presented. The purpose is to redesign the company’s current strategy to ensure further successful developments.The analysis begins with strategic management which forms the basis for the introduction of the main concepts and stages of a strategic management process. Then a comprehensive analysis of an external and internal environment of the company is explained to formulate revised long-term strategies. The results of the internal and external audit identify key areas of the company’s future success, which are customer orientation, implementation of the most modern technologies, ensuring effective and efficient processes, strengthening established partnerships and increasing employee engagement.The methods used in this study are SWOT, IE analysis and QSPM Matrix. The results showed the company’s business was in a position of grow and built and SO strategy were chosen because the strength could be a barrier to competitors and the industry opportunities that the company could use to expand the company. QSPM Matrix results market development strategy as the company’s main strategy.